Cyanobacterial symbionts diverged in the late Cretaceous towards lineage-specific nitrogen fixation factories in single-celled phytoplankton - Francisco M. Cornejo-Castillo (Nature Portfolio, 2016)
Nitrogen fixation in oceans is facilitated by associations between marine phytoplankton and cyanobacteria such as UCYN-A. Here, Cornejo-Castillo et al. show that UCYN-A diversified in the late Cretaceous under strong purifying selection to become lineage-specific symbiont partners with different prymnesiophytes.